Sosialisasi dan Praktik Latihan Teknik Dasar Bermain Futsal bagi Siswa SD Negeri 3 Jeumpa Kabupaten Bireuen - Hidayat, Syukran; Iskandar, Iskandar; Tawakal, Tawakal (LPPM Umuslim, 2023)
Futsal is one of the many sports that is popular with society today besides football. Various aspects support the success of playing futsal such as physical, technical, tactical and mental aspects. Technique is an integral part of the sport of futsal, including passing, controlling, dribbling and shooting, which supports the success of tactics to achieve game goals. Therefore, socialization, guidance and training are correct and directed so that the substance and rules contained in the game of futsal are known and implemented by the players. Especially for beginners. So socialization and training were carried out in the service activities of lecturers and Physical Education teachers for students at SDN 3 Jeumpa, Bireuen Regency. The material is related to the basic rules and techniques in the game of futsal. As a result of socialization and training, participants understand and can practice the correct way to play futsal.